2018
DOI: 10.1038/s41419-018-0993-z
|View full text |Cite
|
Sign up to set email alerts
|

3D micro-environment regulates NF-κβ dependent adhesion to induce monocyte differentiation

Abstract: Differentiation of monocytes entails their relocation from blood to the tissue, hence accompanied by an altered physicochemical micro-environment. While the mechanism by which the biochemical make-up of the micro-environment induces differentiation is known, the fluid-like to gel-like transition in the physical micro-environment is not well understood. Monocytes maintain non-adherent state to prevent differentiation. We establish that irrespective of the chemical makeup, a 3D gel-like micro-environment induces… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 49 publications
4
26
0
Order By: Relevance
“…Our previous publications depict that the MAPK-NF signaling pathway is a crucial regulator of monocyte to macrophage differentiation [45,46].Commensuratewith other reports, we have also shown that inhibition of the activation of this signaling cascade abates differentiation.In this manuscript, our results suggest that hopanoids treatment also leads to the activation of MAPK-NFsignaling pathway for the induction of monocyte to macrophage differentiation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our previous publications depict that the MAPK-NF signaling pathway is a crucial regulator of monocyte to macrophage differentiation [45,46].Commensuratewith other reports, we have also shown that inhibition of the activation of this signaling cascade abates differentiation.In this manuscript, our results suggest that hopanoids treatment also leads to the activation of MAPK-NFsignaling pathway for the induction of monocyte to macrophage differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…The differentiation process is ushered by the activation of a variety of signaling networks that command the various cellular changes. We along with other groups havealsoreported a plethora of signaling molecules contributing to the differentiation process notably MAP kinases and NF- [45,46]. We investigated the involvement of these signaling molecules in the differentiation process induced by the probable hopanoids and our Western blot data suggests the occurrence of phosphorylation of P42/44, P38 MAP kinases as well as NFκwhen treated with the probable hopanoidsvs the untreated control (Fig.6A).…”
Section: Elucidation Of Signaling Cascade Involved In the Monocyte Tomentioning
confidence: 74%
See 1 more Smart Citation
“…In our model, we avoided the adherence of monocytes to the plate surface, and all harvested cells were non-adherent. According to the described adhesion cascade [ 23 ] and the absence of additional inflammatory stimuli such as interferon-gamma or IL-4 [ 6 ], a differentiation of GM-CSF-activated monocytes to macrophages under dynamic but not under static conditions seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has supposed macrophages secrete cytokines, such as TGFβ, to induce the proliferation and EMT process of BPH-1 cells via co-culture of BPH-1 cells with macrophages (31). LPS was established as a chemical inducer to differentiate THP-1 cells into macrophages (32). Therefore, LPS was used for differentiation of THP-1 cells in our study.…”
Section: Discussionmentioning
confidence: 99%